Age-, sex- and tactic-specific kleptoparasitic performance in a long-lived seabird - García, Germán Oscar; Paterlini, Carla Ángela; Favero, Marco; Becker, Peter H.; Bouwhuis, Sandra (Journal of Ornithology)
Kleptoparasitism is an exploitative foraging strategy used across taxa, but factors underlying variation in the foraging performance of individuals using it have not often been addressed. Using longitudinal data on Common Terns stealing food from conspecifics during breeding, we show that variation in the energetic reward of kleptoparasitic behaviour is explained by interactive effects of sex and the attack tactic used by the parasite, as well as by age. Males obtain a higher reward when using an aerial than a terrestrial attack tactic, with decomposition analyses showing that this is due to the energy content of chased after prey items being higher in their aerial attacks. On the other hand, females obtain a higher reward when attacking terrestrially, which is due to their success rate being higher on land than in the air. In addition, the birds show decelerating within-individual improvement with age, which is due to individuals chasing after prey with a higher energy content as they grow older. Our study not only pinpoints factors underlying variation in the foraging performance of kleptoparasites, but also illustrates the importance of modelling individual variation when analyzing foraging performance. Fil: García, Germán Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Paterlini, Carla Ángela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Favero, Marco. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de ...